Вы находитесь на странице: 1из 3

.


.
I.

, :
: > 0 N () N : n > N |fn A| <
lim fn = A.

: > 0 : () > 0 : x E, 0 < |x a| <


|f (x) A| <

lim f (x) = A. a (
xa

, , E ).
() > 0 : x E, 0 < |x | < x0 () : x E x > x0 .
:
> 0 x0 () : x E x > x0 |f (x) A| <

lim f (x) = A

, (
), (,
,
).
, , , .
. :
Th

. fn ,
n n. f (x),
fn N R, ,
.

II.

1. , ,
!
: ,
, :
(a) {xn } a n

{f (xn )} 9;
(b) {xn } a {yn } a,
n

{f (xn )} b {f (yn )} c, b 6= c.
n

, .
2. , E. ,
R E N.
1

. a X 0 X, X.
. a
X 0 ,
X,
a X. ,
N. , N E, , a E,
.
:
I
. lim f (x) = b.
x

{xn }, , {f (xn )} b.
n

, (.. x1 = 1, x2 =
2, . . . , xi = i, . . .) , ,
lim f (xn ) = lim fn = b.

, .

III.

:
2

1. lim n arccos n2n+1 .


n

: lim x arccos x2x+1 , R.


x+


2
x
x2
lim x arccos 2
= lim x arcsin 1
=
x+
x + 1 x+
x2 + 1

2x2 +1
2
arcsin
2x + 1
2x2 + 1
x2 +1

= lim x
(1)
= lim x arcsin 2

2x2 +1
x+
x+
x +1
x2 + 1
2
2

x +1

, :

lim

x+

x 2+
2x2 + 1
=
lim
x+
x2 + 1
x2 + 1

lim

x+

2x2 +1
x2 +1

2x2 +1
x2 +1

arcsin

1
x2

q
2+
= lim

x+

x+

1
x2
1
x

2
= lim
=0
x+ x



2x2 + 1

arcsin t


= t = lim
= 1.
= 2
x +1
t0
t

(2)

(3)

:
s

x2
2x2 + 1
x2 (2x2 + 1)
lim x arccos 2
= lim x
=
lim
=
x+
x+
x + 1 x+
x2 + 1
(x2 + 1)2
s
r
4
2

2 + x12
2x + x
= lim
=
lim
=
2. (4)
x+
x+ 1 + 22 + 14
x4 + 2x2 + 1
x
x
, ,

2.
2

2,

2. , lim
n
:


lim

x+

1 + sin x2
1 sin x2

x

, :


= lim

x+

3
1+sin
1sin

2
n
2
n

n

. -

2
2 sin x
2
1sin x
2
2 sin x
2
1sin x

x

2 sin x2
= lim 1 +
=
x+
1 sin x2
x 2 sin x22

1
1sin x


2
2 sin x
2 sin x2
2
1sin
x
(5)
= lim 1 +
x+
1 sin x2

2 sin x2
1+
1 sin x2

x

2 sin x2
0
lim
= 0.
= lim
x+ 1 sin 2
x+ 1
x

(6)




 2 sin1 x2
2 sin x2

2 sin x2
2
1sin x

= lim(1 + t) 1t = e.
lim 1 +
=
=
t
2
2

t0
x+
1 sin x
1 sin x

(7)

:
lim x

x+

sin x2
2 sin x2
2
=
lim
4

=
lim
2x

sin
= 4.
2
x+
x x+
1 sin x2
x

(8)

e4 .
, , .
!